Waveguides fabrication by femtosecond laser in Tb3+/Yb3+ doped CaLiBO glasses. (August 2021) - Santos, S.N.C.; Almeida, G.F.B.; Almeida, J.M.P.; Hernandes, A.C.; Mendonça, C.R.
Highlights: Waveguides in CaLiBO glasses co-doped with Tb 3+ /Yb 3+ by femtosecond laser. Coupling at 632.8 nm wavelength, the waveguides can support single-mode orientation. CaLiBO waveguides are able to guide the emission of Tb 3+ ions. Abstract: Borate glasses present the ability to host various modifier ions and, therefore, are adaptable for a wide range of applications. Specifically, calcium-lithium tetraborate (CaLiBO) glasses doped with rare earths have been investigated for applications involving energy transfer processes. In this work, waveguides were inscribed by femtosecond laser microfabrication in CaLiBO glasses containing Tb 3+ and Yb 3+ ions, displaying emission in the green region. Single-mode guiding at 632.8 nm, with propagation losses of approximately 2.0 dB/cm, was obtained in 7.0-mm long waveguides with a diameter on the order of 2 μm, produced in the glass bulk, at approximately 100 μm below the sample surface. By coupling 488 nm light, the fabricated waveguide showed the capability of guiding the typical emission of Tb 3+ ions. Such glasses containing rare earths could be suitable for the development of green light-emitting microdevices.